METHODOLOGY AND ANALYSIS, ORGANIZATION AND CONDUCT OF PEDAGOGICAL EXPERIMENTAL PROCESSES (Web of Teachers: Inderscience Research, 2024)
The purpose of organizing the pedagogical trial test is to increase the level of knowledge of students, to achieve the quality and efficiency of education by providing the pedagogical conditions for the organization of innovative schools. In this article, the method of conducting necessary pedagogical experiments for the quality of education to achieve high results is highlighted.